On information, priors, econometrics, and economic modeling - Venegas Martínez, Francisco; De Alba, Enrique; Ordorica Mellado, Manuel (Estudios Económicos de El Colegio de México, 1999)
This paper attempts to reconcile all inferential methods which by maximizing a criterion functional produce non - informative and informative priors. In particular, Good' s (1968) Minima x Evidence Priors, MEP, Zellner's (1971) Maxima l Data Information Priors, MDIP, and Bernardo's (1979) Reference Priors, RP, are seen as special cases of maximizing a more general criterion functional. In a unifying approach Good-Bernardo-Zellner priors are introduced and applied to a number of Bayesian inference procedures which are useful in economic research, such as the Kalman Filter and the Normal Linear Model. We also use the GoodBernardo-Zellner distributions in several economic models.